Gut microbiota and inflammasome-mediated pyroptosis: a bibliometric analysis from 2014 to 2023 - Zhang, Hang; Zhao, Tian; Gu, Juan; Tang, Fushan; Zhu, Lei (Frontiers in Microbiology, 2025)
BackgroundThe role of gut microbiota in inflammatory disease development and progression has been recognized more recently. Inflammasome-mediated pyroptosis in involved in these diseases. This complex relationship between gut microbiota and inflammasome-mediated pyroptosis provides an important field of research. Bibliometric analysis provides a comprehensive understanding of this relationship, offering valuable insights into emerging research trends.Materials and methodsLeveraging data spanning from 2014 to 2023 sourced from the Web of Science Core Collection, our analysis was conducted using advanced tools such as SCImago Graphica, VOSviewer, and CiteSpace software. Visualizations were created using GraphPad Prism software. We explored the nuanced aspects of research hotspots, collaborative networks, and developing trends in this field.ResultsA global bibliometric analysis identified 520 relevant studies spanning 41 countries and 887 institutions. Over the past decade, publication trends have shown consistent growth, with China and the United States leading the research output. Southern Medical University and Nanjing Medical University in China emerged as leading institutions in this filed. Prominent contributors include Jia Sun, Yuan Zhang, Wei Chen, Jing Wang, and Hongtao Liu from China, alongside Eicke Latz from Germany. High-impact journals such as Frontiers in Immunology and Nature Communications have been pivotal in disseminating research in this domain. Keyword analysis highlighted a primary focus on gut microbiota, NLRP3 inflammasome, pyroptosis pathways, and inflammatory diseases, themes that persist in recent studies. Furthermore, burst keyword analysis identified “butyrate” as the sole term currently experiencing a marked increase in research interest.ConclusionResearch has been deeply focused on the gut microbiota and inflammasome triggered pyroptosis in years. Over the past decade, the exploration of how gut microbiota and NLRP3 or NLRP6 inflammasome-mediated pyroptosis has been an area of interest. Future investigations in this filed may primarily revolve around understanding the correlation between butyrate and NLRP3 inflammasome induced pyroptosis in relation to conditions. However, an in-depth analysis, through studies is crucial to uncover and elucidate the complex mechanisms linking these elements.